Peningkatan Hasil Belajar PAI Siswa kelas IV Menggunakan Metode Make A Match di UPTD SDN 04 Simpang Kapuak - Dela Zulfitri; Martina Iriani; Roza Elfira; Desri Wahyuni; Fadhila Yusri; Adi Warman (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This research aims to improve student learning outcomes in the material Emulating Asmaul Husna by aplying the make a match learning method in class IV UPTD SDN 04 Simpang Kapuak with the variable that is the target of change in this research is learning outcomes, while the action variable used in this research is a make a match learning method. This research is classroom action research carried out in 2 cycles, each cycle consisting of 4 stages, namely planning, implementation/action, observation/observation, and reflection. The data collection techniques used are observation, interviews, documents and tests. Based on the research results, it can be concluded that student learning outcomes continue to increase until they reach a significant increase. Student learning outcomes in the pre-action stage were 38.5%, in cycle I (first) it increased to 61.5%, in cycle II (second) it also increased to 92.30%. Thus, a recommendation can be put forward that the application of the make a match learning method can improve student learning outcomes in the material Emulating Asmaul Husna for the 2024/2025 academic year. Keywords: , I